Students2019; Perceptions of the Effectiveness of Teaching Listening Skills to English Foreign Language Students at Three Ethiopian Universities (Global Journal of Human-Social Science, 2018)
he listening skill plays a decisive role in our day-today communication Hedge 2000 found that up to 45 of one s communication time is spent on listening activities while Chen 2011 estimates that 50 of an adult s communication consists of listening It is thus clear that one spends much more time on listening communication activities than on the rest of the language skills i e reading writing and speaking The fact that people spend so much time on listening however does not imply that they are good listeners It is rather an indication of how important it is that their listening skills should be developed and that time should be spent on the teaching of this important communication skill to ensure effective communication The role that listening plays in the acquisition of a second or foreign language started to gain attention when the Communicative Language Teaching methodology which emphasised the need of teaching listening for effective oral communication Goh 2008 became popular in language teaching in the 1970s Although much ground-breaking work on the teaching of listening in second and foreign languages has been done it is still one of the skills that receive little attention in many classes which is a challenge for learners in the classroom and beyond Vandergrift Goh 2012